Perception and Impacts to Climate Emergency in Maiduguri Urban, North-East Nigeria: A Case for Community Based Adaptation Approach - Nkwocha, Kelechi Friday; Akanwa, Angela Oyilieze; Jimme, Mohammed Abba; Iheukwumere, Samuel Oji; Joe-Nkechebelu, Ngozi (Review of Environment and Earth Sciences, 2020)
Presently, a global climate emergency has been declared due to human lifestyles that have released anti- friendly gases into the atmosphere. This timely study captures the vulnerable climate aggression in Northern Nigeria and the need for adaptation for formidable climate actions. The study assessed the climate emergency perception using a community based adaptation/participatory approach in Maiduguri urban. The study employed the use of survey approach which included the random sampling of 300 structured questionnaires, observation, focus group discussion and interview of key informants. Findings from the study showed that 60% of the residents were aware of climate crisis especially in high income areas. Also, 24.7%, 19.3%, 18% and 17% agreed that deforestation; household activities, industrialization and urbanization are major factors that aid climate change in the study area respectively. Findings from FGD and oral interviews showed that there is increased temperature, rainfall unpredictability and heat intensity. Further, they indicated that the increased heat seasons have triggered health risks in low income areas affecting mostly young children and the aged. The study also revealed that only 9% of the respondents were women while 81% were men. Obviously, the little role of women may be a huge setback on taking adaptive climate actions since 86% of respondents agreed that household activities are a major contributor to climate emergency. To address this challenge this study recommended the Community based adaptation/participatory strategy (CBA/P) which is all inclusive and participatory tool that will promote the health and well-being of the community from climate crisis.